2021
DOI: 10.1097/pr9.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of central relaxin receptor activation on persistent inflammatory pain in mice: behavioral and neurochemical data

Abstract: Supplemental Digital Content is Available in the Text. Relaxin peptide analogues produce strong but transient analgesia in inflammatory pain in mouse. Relaxin and its RXFP1 receptor represent a new peptidergic system that modulates pain processing in the forebrain areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…1 D , 3 ) stimuli at 4 d post-CFA. Swiss mice thresholds were consistent with those obtained in C57/Bl6 mice in another recent study ( 31 ), although they were seemingly higher in Swiss mice than in C57/Bl6 mice due to weight/size differences ( 32 ). The 6-OHDA mice exhibited a further decrease in thermal ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…1 D , 3 ) stimuli at 4 d post-CFA. Swiss mice thresholds were consistent with those obtained in C57/Bl6 mice in another recent study ( 31 ), although they were seemingly higher in Swiss mice than in C57/Bl6 mice due to weight/size differences ( 32 ). The 6-OHDA mice exhibited a further decrease in thermal ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…These numerous effects of relaxin are consistent with the expression pattern of its cognate receptor, RXFP1 239, 245, 246 . Notably, despite some early mapping studies of RXFP1 mRNA and binding sites in several tissues including the heart and brain, 215,247,248 few studies have explored the role of relaxin/RXFP1 signaling in brain function 249–252 …”
Section: Insulin‐like (Relaxin)‐family Peptide and Receptor Systemsmentioning
confidence: 68%
“…239,245,246 Notably, despite some early mapping studies of RXFP1 mRNA and binding sites in several tissues including the heart and brain, 215,247,248 few studies have explored the role of relaxin/RXFP1 signaling in brain function. [249][250][251][252] The INSL3/RXFP2 system was initially identified as having a clear role in male reproduction, specifically in the development of the gubernaculum and testicular descent, because INSL3 is highly expressed in testicular Leydig cells in animals and human 253 and both…”
Section: Recent Advances and Current Anatomical And Functional Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed that several genes exhibited noticeable batch-related variance, though it tended to be smaller in magnitude compared to cell-type variance ( Supplementary Figure 3A ). To begin, we analyzed the effect of Crescendo on three genes that were cell-type specific: Gpr34 in microglia cells 40,41 , Rxfp1 42,43 in cortical excitatory neurons, and Epha8 44 in striatal inhibitory neurons. Each of these genes were subject to technical effects ( Figure 2D, 2G , Supplementary Figure 4A-E ).…”
Section: Resultsmentioning
confidence: 99%